Analisa Morfologi, Serap Bunyi dan Kekuatan Tarik Biokomposit Getah Pinus dan Serbuk Kayu Jati dengan Perlakuan NaOH - Ikromuddin, Hafidz; Suardana, NPG; Kencanawati, CIPK (Teknik Desain Mekanika; Vol 10 No 4 (2021): Oktober 2021 : Teknik Desain Mekanika, 2021)
Abstract The need for good materials requires scientists to use natural and artificial material waste to be processed into more useful things. Variations in NaOH treatment are without immersion, 5%, 10% and 15% NaOH. Large percentage of fusion uses volume fraction with teak powder by 65% and pine resin matrix by 35%. The size of teak wood powder used is 8 mesh ? a ? 7 mesh. Noise absorption testing using two microphone impedance tubes with ISO 10534-2: 1998 and ASTM E:1050:1998 standards. The tensile test is performed with a tool with astm standard D 638-03. The results of the test obtained the highest sound absorption strength in specimen concentrations of 5% NaOH with a value of 0.69 at a frequency of 300 Hz. The maximum pressure value and also the highest strain are at the concentration of 5% NaOH of 4.28 MPa and 5.00% Keywords : NaOH, Teak Wood Powder, Pine Resin, Biocomposite